2012
DOI: 10.1007/s00227-012-1937-2
|View full text |Cite
|
Sign up to set email alerts
|

Foraging grounds, movement patterns and habitat connectivity of juvenile loggerhead turtles (Caretta caretta) tracked from the Adriatic Sea

Abstract: Knowledge about migratory routes and highly frequented areas is a priority for sea turtle conservation, but the movement patterns of juveniles frequenting the Adriatic have not been investigated yet, although juveniles represent the bulk of populations. We tracked by satellite six juvenile and one adult female loggerhead from the north Adriatic. The results indicated that loggerhead juveniles (1) can either show a residential behaviour remaining in the Adriatic throughout the year or perform seasonal migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
69
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 46 publications
(81 reference statements)
13
69
0
Order By: Relevance
“…In general, resident areas of juveniles in oceanic zones are much wider than in neritic zones (Revelles et al 2007b;Cardona et al 2009;Casale et al 2012aCasale et al , 2012b (Figure 4), as also observed for adults in the Mediterranean and elsewhere (Hawkes et al 2006;Schofield et al 2010a). Long-term residence of juveniles in neritic foraging grounds seems more common than in oceanic areas and it has been observed in various locations through tag returns (Casale et al 2007a;Revelles et al 2008) and satellite tracking Cardona et al 2009;Hochscheid et al 2010;Casale et al 2012aCasale et al , 2012bHochscheid et al 2013) (Figure 3). The juvenile neritic foraging sites are, however, usually larger than the adult neritic sites, with juveniles showing a propensity to wander over quite large areas (e.g.…”
Section: Large Juvenilessupporting
confidence: 60%
See 4 more Smart Citations
“…In general, resident areas of juveniles in oceanic zones are much wider than in neritic zones (Revelles et al 2007b;Cardona et al 2009;Casale et al 2012aCasale et al , 2012b (Figure 4), as also observed for adults in the Mediterranean and elsewhere (Hawkes et al 2006;Schofield et al 2010a). Long-term residence of juveniles in neritic foraging grounds seems more common than in oceanic areas and it has been observed in various locations through tag returns (Casale et al 2007a;Revelles et al 2008) and satellite tracking Cardona et al 2009;Hochscheid et al 2010;Casale et al 2012aCasale et al , 2012bHochscheid et al 2013) (Figure 3). The juvenile neritic foraging sites are, however, usually larger than the adult neritic sites, with juveniles showing a propensity to wander over quite large areas (e.g.…”
Section: Large Juvenilessupporting
confidence: 60%
“…A degree of permanence in the same area was indicated by tag returns in the western and eastern Mediterranean (Casale et al 2007a), and was directly observed through satellite tracking in some cases in the western Mediterranean (Revelles et al 2007a) but not in others, either in the western (Cardona et al 2005;Eckert et al 2008;Cardona et al 2009) or in the eastern Mediterranean (Bentivegna 2002). In general, resident areas of juveniles in oceanic zones are much wider than in neritic zones (Revelles et al 2007b;Cardona et al 2009;Casale et al 2012aCasale et al , 2012b (Figure 4), as also observed for adults in the Mediterranean and elsewhere (Hawkes et al 2006;Schofield et al 2010a). Long-term residence of juveniles in neritic foraging grounds seems more common than in oceanic areas and it has been observed in various locations through tag returns (Casale et al 2007a;Revelles et al 2008) and satellite tracking Cardona et al 2009;Hochscheid et al 2010;Casale et al 2012aCasale et al , 2012bHochscheid et al 2013) (Figure 3).…”
Section: Large Juvenilesmentioning
confidence: 83%
See 3 more Smart Citations